Reward strategies and job satisfaction in private companies: a case of Uganda Breweries-Luzira - Ochwo, Boniface Okello; Mwesigwa, David (Annals of Human Resource Management Research, 2021)
Purpose: This study aimed to determine the relationship between reward structures and employee job satisfaction at Uganda Breweries, Port Bell in Luzira. Research methodology: It was cross-sectional, quantitative though involving qualitative elements. The study involved 150 respondents sampled using purposive and convenience sampling strategies. Data was collected using a self-administered questionnaire and an interview guide. The findings reveal a significant positive relationship between financial rewards structures and employees' job satisfaction at Uganda Breweries. Results: The findings suggest a significant positive relationship between non-financial rewards structures and employees' job satisfaction at Uganda Breweries Port Bell at Luzira. The findings further advocate for enhanced attention linking promotions to job satisfaction of employees at Uganda Breweries. It is concluded that financial rewards, non-financial reward strategies and promotions had a highly positive significant relationship on employee job satisfaction at Uganda Breweries-Luzira. Limitation: This study was limited to Uganda Breweries at Port Bell, a private company and so its findings may not easily be generalised across organisations. Contribution: The results can be useful to private-sector managers. Keywords: Financial rewards, Non-financial reward, Job satisfaction, Decision-making, Income